2017
DOI: 10.1371/journal.pone.0172799
|View full text |Cite
|
Sign up to set email alerts
|

A relationship to survival is seen by combining the factors of mismatch repair status, tumor location and age of onset in colorectal cancer patients

Abstract: BackgroundThe progression of colorectal cancer (CRC) may differ depending on the location of the tumor and the age of onset of the disease. Previous studies also suggested that the molecular basis of CRC varies with tumor location, which could affect the clinical management of patients. Therefore, we performed survival analysis looking at different age groups and mismatch repair status (MMR) of CRC patients according to primary tumor location in an attempt to identify subgroups of CRC that might help in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Since CAS measures intra-tumoral immune cytolytic activity, it makes sense to see high CAS associating with high TIL conditions such as MSI-H CRC. Patients with MSI-H tumors have also been found in several studies to have improved survival compared to their MSS counterparts 1,5 . This may be attributed to the elevation in cytolytic activity within their cancer cells secondary to increased TIL infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CAS measures intra-tumoral immune cytolytic activity, it makes sense to see high CAS associating with high TIL conditions such as MSI-H CRC. Patients with MSI-H tumors have also been found in several studies to have improved survival compared to their MSS counterparts 1,5 . This may be attributed to the elevation in cytolytic activity within their cancer cells secondary to increased TIL infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the fourth most common cause of cancer related death 1,2 . Impaired DNA repair mechanisms and genomic instability are key factors in carcinogenesis via the accumulation of somatic mutations within DNA 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In general, dMMR is more frequent in right-sided CC than in left-sided CRC and is associated with better survival than pMMR. 17 Therefore, this study aimed to investigate the clinicopathologic differences according to the immunosurveillance pattern between right-sided and left-sided CRC, using IHC staining of MMR proteins to identify biomarkers and prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 For instance, it was reported that microsatellite-stable (MSS) CRC had a distinct phenotype such as left-sided location. 23 , 24 All of our results suggested that STC2 might contribute to the tumorigenesis or progression of CRC.…”
Section: Discussionmentioning
confidence: 65%